2018
DOI: 10.1016/j.ajog.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth velocity: the NICHD fetal growth studies

Abstract: We provide fetal growth velocity data to complement our previous work on fetal growth size standards, and have developed a calculator to compute fetal growth velocity. Preliminary findings suggest that growth velocity adds additional information over knowing fetal size alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 23 publications
3
71
3
1
Order By: Relevance
“…International percentile curves for EFW, calculated after studies of fetuses in Anglo-Saxon countries and used to check the week-adapted weight of the unborn fetuses worldwide, may not be the right strategy because they pursue a one-size-fits-all policy in approaching what is too large or too small [25, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International percentile curves for EFW, calculated after studies of fetuses in Anglo-Saxon countries and used to check the week-adapted weight of the unborn fetuses worldwide, may not be the right strategy because they pursue a one-size-fits-all policy in approaching what is too large or too small [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Goetzinger et al reported a lack of accuracy in fetal weight estimation when using Leopold’s manoeuvres [35]. Several prospective studies were able to show advantages of clinical palpation like Leopold’s manoeuvres in predicting fetal macrosomia [14, 26, 36, 37], and the accuracy of fetal weight estimation when using ultrasound biometry has been shown to be no better than that of Leopold’s manoeuvres [21]. Still other studies report an advantage for them for fetal weight estimation [3844].…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria included maternal age 18–40 years; pre-gravid body mass index (BMI) 19.0–29.9 kg/m 2 calculated from recalled pre-pregnancy weight and height; viable singleton pregnancy between 8 weeks 0 days (8w0d) to 13 weeks 6 days with gestational age consistent with the last menstrual period dating within a prescribed range per screening sonogram. Women with prior adverse pregnancy outcomes, history of chronic disease, conception using medical drugs or assisted reproductive technology, cigarette smoking, illicit drug use or intake of ≥1 alcoholic drinks per day were excluded, as previously described [ 2 , 4 ]. For the Fetal Growth Standard, we also excluded women with pregnancy complications, including preterm delivery (<37 weeks), gestational diabetes, and hypertensive diseases, as well as neonatal conditions including congenital anomalies and death [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NICHD Fetal Growth Studies–Singletons was a prospective cohort study designed to establish standards of fetal growth and determine the need for racial/ethnic specific standards [ 2 ]. Significant racial/ethnic differences in fetal growth, fetal growth velocity, and birthweight were observed even after adjusting for detailed demographic and socioeconomic factors that differed among the groups including insurance, annual income, education, and marital status [ 3 , 4 ]. However, whether race/ethnic differences in birthweight varied by these socioeconomic factors was not directly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies or other reports, birthweight or its cross-sectional standardized score of body size has been generally utilized for fetal growth assessment. Although there is no objection that birthweight is indeed a valuable parameter, recent studies have shown that growth velocity provides additional information over knowing fetal size alone 4,5 . Considering the biological aspect, fetal growth velocity reflects the fetal response to various conditions during the developmental process within the maternal constraint 1,6 .…”
Section: Introductionmentioning
confidence: 99%